Compliance to Antihypertensive Medication and Associated Factors among Hypertensive Chronic Kidney Disease Patient Attending at a Tertiary Care Level Hospital (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Achieving optimal blood pressure control remains a challenge in hypertensive chronic kidney disease patients, however monitoring and improving medication compliance would be a very useful tool to improve outcomes and to reduce the risk of complications like end-stage renal disease, cardiovascular disease and cerebrovascular accidents. Factors associated to compliance have importance for successful treatment of patients to prevent jeopardize of the goal of treatment.Objectives: To determine the proportion of treatment compliance among hypertensive chronic kidney disease patients.Method: An observational cross-sectional study was conducted in the department of Nephrology of Dhaka Medical College Hospital from January 2022 to December 2022. 264 hypertensive CKD patients were included in this study. Structured questionnaire was used to collect patients information like socio-demographic and behavioral characteristics, clinical history and prescribed antihypertensive medication. Collected data analyzed by using SPSS 26.0. P value of < 0.05 was significant.Result: Among 264 CKD patients 58% male, 42% female and 27.3% patients were in 51-60 years age group. Only 32.1% patient achieved BP (